Minor amputation does not negatively affect health‐related quality of life as compared with conservative treatment in patients with a diabetic foot ulcer: An observational study. Issue 3 (30th November 2016) - Pickwell, K.; Siersma, V.; Kars, M.; Apelqvist, J.; Bakker, K.; Edmonds, M.; Holstein, P.; Jirkovská, A.; Jude, E.B.; Mauricio, D.; Piaggesi, A.; Reike, H.; et al.
Abstract: Background: Health‐related quality of life (HRQoL) is poor in patients with persistent diabetic foot ulcers and poor HRQoL predicts worse outcomes in these patients. Amputation is often considered a treatment failure, which is why conservative treatment is generally preferred over amputation. However, it is unclear whether minor amputation negatively affects HRQoL compared with conservative treatment in patients with diabetic foot ulcers. Methods: In the cohort of the multicenter, prospective, observational Eurodiale study, we determined difference in change of HRQoL measured by EQ‐5D between patients with a diabetic foot ulcers that healed after conservative treatment (n = 676) and after minor amputation (n = 145). Propensity score was used to adjust for known confounders, attempting to overcome lack of randomization. Results: Baseline HRQoL was not significantly different between patients treated conservatively and undergoing minor amputation. In addition, there was no difference in the change of HRQoL between these groups. In patients who healed 6 to 12 months after the first visit, HRQoL on the anxiety/depression subscale even appeared to improve more in those who underwent minor amputation. Conclusions: Minor amputation was not associated with a negative impact on HRQoL in patients with a diabetic foot ulcers. It may therefore not be considered treatment failure in terms of HRQoL but rather a viable treatment option. A randomized controlled trial is warranted to further examine the influence of minor amputations on health‐related quality of life.